Macroeconomic Changes And Prices Stock In Real Estate And Property Firm - Rita Indah Mustikowati; Sri Wilujeng; M Yusuf Kurniawan (Jurnal Studi Manajemen dan Bisnis, 2020)
This research was conducted to examine changes in macroeconomic conditions on stock prices in real estate and property companies. The aim of this research is to explain the changes in macroeconomic conditions on the stock prices of real estate and property companies. The sampling technique used was purposive sampling with a sample of 14 companies from 48 real estate and property companies listed on the JSX. The analysis technique used is multiple regression. Based on the results of the analysis, it was found that changes in macroeconomic conditions, namely inflation, had no positive effect on the stock prices of real estate and property companies. This is because the amount of demand for real estate and property will increase in accordance with population growth. Other findings show that the interest rate proxied from the BI Rate has a negative effect on the stock prices of real estate and property companies. Increased interest rates from the BI Rate will cause investors to be no longer interested in investing in the money market because it is considered more profitable to invest with high interest rates.